2014
DOI: 10.3892/or.2014.3368
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone inhibits constitutive NF-κB activation and induces reactive oxygen species-mediated apoptosis in osteosarcoma U2OS cells through mitochondrial dysfunction

Abstract: Abstract.Human osteosarcoma is an aggressive tumor which frequently resists chemotherapy; therefore, the search for new agents for its treatment is of great importance. Isoalantolactone, isolated from Inula spp., has been reported to inhibit the growth of several types of cancer cells. However, no prior research has been conducted to demonstrate the antiproliferative potential of isoalantolactone on osteosarcoma. The present study is the first to investigate the effects of isoalantolactone on cell viability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Cell cycle progression is one of the major regulatory mechanisms for cell growth. 20 To gain further insight into mechanism underlying antiproliferative and cytotoxic effect of Brv-A, we investigated cell cycle phase profile in Brv-A treated cells in presence or absence of NAC. Flow cytometry analysis showed that Brv-A arrested MCF-7 cells in G 2 /M phase in dosedependent manner.…”
Section: Brv-a Induces Ros Dependent G 2 /M Phase Arrest In Mcf-7 Cellsmentioning
confidence: 99%
“…Cell cycle progression is one of the major regulatory mechanisms for cell growth. 20 To gain further insight into mechanism underlying antiproliferative and cytotoxic effect of Brv-A, we investigated cell cycle phase profile in Brv-A treated cells in presence or absence of NAC. Flow cytometry analysis showed that Brv-A arrested MCF-7 cells in G 2 /M phase in dosedependent manner.…”
Section: Brv-a Induces Ros Dependent G 2 /M Phase Arrest In Mcf-7 Cellsmentioning
confidence: 99%
“…34 In addition, IAL was recently identified as selectively toxic to cancer cells. 18,35 These results suggested that IAL is a multiple biological compound, as a drug, used in clinical practice. However, IAL is not soluble in water, which limited its pharmacological activity in vitro/in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, this compound has been reported to significantly induce breast cancer cell apoptosis by activating the caspase cascade, cleaving poly (ADP‐ribose) polymerase . In addition, IAL was recently identified as selectively toxic to cancer cells . These results suggested that IAL is a multiple biological compound, as a drug, used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations